(untitled) (Research, Society and Development, 2022)
Lips are the focal point of the lower third of the face, and are capable of transmitting beauty and sensuality. Even with the great visual impact on the face, the lips are vulnerable to the aging process, which makes alternatives to circumvent the loss of volume and perioral wrinkles necessary. With this, there are several techniques for filling and lip sculpting. The aim of this article is to describe the main lip sculpting and filling techniques, analyzing the risks and complications involved. This is an integrative literature review, and articles from the last seven years related to the subject were searched in the PubMed, LILACS, Scielo and Scopus databases, using the keywords: "lip filler", "lip sculpture" and the search terms in English: "lip filler", "hyaluronic acid", "technique". Twenty-one articles were selected from the searches and with the application of the inclusion and exclusion criteria. Among the techniques, the following stand out: serial puncture technique, bolus technique, anterograde and retrograde linear tapping technique, anterograde and retrograde technique, tunneling technique, and linear injection technique. It is important that the dental surgeon is aware of how to correctly execute a technique and its purpose, so that he/she can understand and avoid the risks and failures of the procedure.